The Evolution of Alternative Buoyancy Mechanisms in Freshwater Fish Eggs - Chen, Feng; Smith, Carl; Wang, Yeke; He, Jun; Xia, Wulai; Xue, Ge; Chen, Jun; Xie, Ping (Frontiers in Ecology and Evolution, 2021)
Alternative reproductive tactics (ARTs) are behavioural, morphological, and physiological traits associated with alternative reproductive phenotypes within a population or species. ARTs are widespread in nature, and are a particular feature of teleost fishes. However, few studies have examined egg buoyancy mechanisms in the context of the evolution of ARTs in freshwater fishes. In marine fishes, egg buoyancy is achieved chiefly through hydration. While the buoyancy of freshwater fish eggs has been suggested to be determined primarily through the presence of oil droplets, the majority (60%) of freshwater pelagic eggs do not possess an oil droplet. We applied a physical model of buoyancy to understand the contributions of oil droplets and hydration to the buoyancy of pelagic freshwater fish eggs. We further used phylogenetic regression to estimate the effect of the relative size of the perivitelline space, habitat and parental care on the occurrence of oil droplets, while controlling for non-independence among species due to phylogenetic relatedness. Our analysis demonstrates that the probability of oil droplets in freshwater pelagic eggs exhibits a significant negative relationship with the size of perivitelline space, which may reflect a trade-off relating to energy allocation in contrasting habitats. We also demonstrate a positive association between the probability of oil droplets and the provision of parental care and occupancy of lentic habitats. These findings indicate the evolution of contrasting buoyancy mechanisms as novel ARTs in freshwater fishes. A theoretical model in combination with empirical analysis indicate the evolution of novel ARTs in freshwater fishes as adaptive responses to flow conditions.